Rudyard Kipling and Representation of Language Family in the World: A Study of the Philosophy of Language - Rohman, Saifur; Suhono, Suhono; Marliana, N. Lia (CV. Creative Tugu Pena, 2023)
The paper is to explain linguistical image of Rudyard Kipling in the poetry “The Ballad of East and West” and to relate with family of language over the world. It is found, the words “west” and “east” refer to the different location but it is from the similar pronunciation. It like “atala” in Sanskrit, “od” in Greek, and has relation with the word “Atlantic” in English. The data will be approached by the philosophy of language, particularly in the perspective of the fixed thing (Greek: esse) and the changed thing (percipi). The result, the word has the same essence. The trace of family of the word “east” and “west” could be proved in the language of Austronesian, particularly in Javanese poem. There is hybridity of reality in the area of language in the world. It could be recommended that an evidence in language is a medium of learning related with education, culture, and reality of Austronesian. Keywords: Philosophy of Language, Language Family, Rudyard Kipling